Phenotyping misophonia: Psychiatric disorders and medical health correlates - Rosenthal, M. Zachary; McMahon, Kibby; Greenleaf, Anna S.; Cassiello-Robbins, Clair; Guetta, Rachel; Trumbull, Jacqueline; Anand, Deepika; Frazer-Abel, Emily S.; Kelley, Lisalynn (Frontiers in Psychology, 2022)
Misophonia is characterized by decreased tolerance to specific sounds and associated stimuli that causes significant psychological distress and impairment in daily functioning (Swedo et al., 2022). Aversive stimuli (often called “triggers”) are commonly repetitive facial (e.g., nose whistling, sniffling, throat clearing) or oral (e.g., eating, drinking, mouth breathing) sounds produced by other humans. Few empirical studies examining the nature and features of misophonia have used clinician-rated structured diagnostic interviews, and none have examined the relationship between misophonia and psychiatric disorders in the Diagnostic and Statistical Manual-5th version (DSM-5; American Psychiatric Association, 2013). In addition, little is known about whether there any medical health problems associated with misophonia. Accordingly, the purpose of the present study was to improve the phenotypic characterization of misophonia by investigating the psychiatric and medical health correlates of this newly defined disorder. Structured diagnostic interviews were used to assess rates of lifetime and current DSM-5 psychiatric disorders in a community sample of 208 adults. The three most commonly diagnosed current psychiatric disorders were: (1) social anxiety disorder, (2) generalized anxiety disorder, and (3) specific phobia. The three most common lifetime psychiatric disorders were major depressive disorder, social anxiety disorder, and generalized anxiety disorder. A series of multiple regression analyses indicated that, among psychiatric disorders that were correlated with misophonia, those that remained significant predictors of misophonia severity after controlling for age and sex were borderline personality disorder, obsessive compulsive disorder, and panic disorder. No medical health problems were significantly positively correlated with misophonia severity.